Targeted NGS: A Cost-Effective Approach to Molecular Diagnosis of PIDs - Stoddard, Jennifer L.; Niemela, Julie E.; Fleisher, Thomas A.; Rosenzweig, Sergio D. (Frontiers in Immunology, 2014)
Background: Primary immunodeficiencies (PIDs) are a diverse group of disorders caused by multiple genetic defects. Obtaining a molecular diagnosis for PID patients using a phenotype-based approach is often complex, expensive, and not always successful. Next-generation sequencing (NGS) methods offer an unbiased genotype-based approach, which can facilitate molecular diagnostics. Objective: To develop an efficient NGS method to identify variants in PID-related genes. Methods: We performed HaloPlex custom target enrichment and NGS using the Ion Torrent PGM to screen 173 genes in 11 healthy controls, 13 PID patients previously evaluated with either an identified mutation or SNP, and 120 patients with undiagnosed PIDs. Sensitivity and specificity were determined by comparing NGS and Sanger sequencing results for 33 patients. Run metrics and coverage analyses were done to identify systematic deficiencies. Results: A molecular diagnosis was identified for 18 of 120 patients who previously lacked a genetic diagnosis, including 9 who had atypical presentations and extensive previous genetic and functional studies. Our NGS method detected variants with 98.1% sensitivity and >99.9% specificity. Uniformity was variable (72-89%) and we were not able to reliably sequence 45 regions (45/2455 or 1.8% of total regions) due to low (<20) average read depth or <90% region coverage; thus, we optimized probe hybridization conditions to improve read-depth and coverage for future analyses, and established criteria to help identify true-positives. Conclusion: While NGS methods are not as sensitive as Sanger sequencing for individual genes, targeted NGS is a cost-effective, first-line genetic test for the evaluation of patients with PIDs. This approach decreases time to diagnosis, increases diagnostic rate, and provides insight into the genotype-phenotype correlation of PIDs in a cost-effective way.